GREEN ACCOUNTING AND ITS IMPACT ON BUSINESS ENVIRONMENT (International Journal of Food and Nutritional Sciences, 2023)
Green Accounting, also known as environmental accounting or sustainable accounting, is asystem of accounting that takes into account the economic, environmental, and social costsand benefits of business activities. It involves measuring and reporting the impacts ofeconomic activities on natural resources and the environment, in addition to traditionalfinancial measures.Green accounting is a crucial financial tool for reducing environmentalcosts. It is a necessary step towards sustainable building. It states that appropriate methodsshould be devised by business organisations to compensate society for environmental damagecommitted in the pursuit of profits. The environment is lagging behind in the race ofeconomic progress. Human exploitation of natural resources has resulted in significantenvironmental issues, including pollution, climate change, global warming, ozone layerdepletion and other natural disasters. The Social environment is an important part of PESTanalysis. Green accounting explains how the corporate sector is harming the environment byits activities and how it can be reduced through timely decision-making. In long run,depletion of natural resources is harming the environment as well as long term availability ofresources for generations to come whereas under GDP analysis these environmental factorsare ignored. Therefore, maintaining a balance between economic development andenvironmental protection is critical at this time. The notion of green market and greenentrepreneurship has also provided both opportunities and threats to business enterprises.Green Accounting considers the environmental cost of operations by identifying andassessing environmental liabilities while preparing financial statements. The purpose of thisstudy is to look how the implementation of concept of environmental accounting will impactthe business environment for the entrepreneurs.